Psychological contract in the volunteer youth sport coach environment: the community sport club perspective. Issue 5 (3rd September 2019) - Harman, Alanna; Doherty, Alison
ABSTRACT: Purpose: In order to provide a more complete understanding of the psychological contract in the volunteer youth sport coach setting, this study advances previous research examining the coaches' psychological contract by exploring community sport clubs' expectations of their coaches, and what they expect to provide in return. Design: Focus groups with three community sport clubs that provide both recreational and competitive team sport programming. Findings: Findings revealed sport clubs have common transactional and relational expectations of themselves and their volunteer coaches. The sport clubs' most important expectations of their volunteer coaches are creating a positive experience for participants (relational) and fulfilling the assigned coaching role (transactional). The most important expectations that sport clubs have of themselves are club administration (transactional) and coach support (relational). There was some variation in the expectations associated with recreational versus competitive level coaches. Additionally, orientation meetings and handbooks are used by the clubs to communicate their expectations. Implications: The findings extend knowledge of the psychological contract in the volunteer youth sport coach setting to the clubs' perspective, and has implications for aligning respective expectations with volunteer coaches, which may impact volunteer retention.